MOMSEN, Janet Henshall ; TOWNSEND, Janet G. Geography of gender in the third world - Cànoves, Gemma (Documents d’Anàlisi Geogràfica, 1989)
MOMSEN, Janet Henshall; TOWNSEND, Janet G. eds., 1987, Geography of Gender in the Third World. Londres, Hutschinson, 411 pp.